Research for effective social work practice - Krysik, Judy (McGraw-Hill, 2007)
This is the fifth and final text in McGraw-Hill's new series NEW DIRECTIONS IN SOCIAL WORK. The text covers the basics of using and conducting social work research in a user-friendly, practical way, and provides many examples of social work research drawn from the literature as well as the authors' many years as social work educators, researchers, and evaluation consultants. Research for Effective Social Work Practice addresses all the basic topics such as formulating research questions, sampling, research design, measurement, and analysis; unlike other texts in the field, however, this book logically links the chapters so that, based on the research question that the social worker selects, she or he will be able to (a) make a reasoned judgment about the best research methods to apply, (b) articulate the strengths and weaknesses of her or his choices, and (c) critique the research methods used in other studies.